Worthwhile Relevance of Infrared Spectroscopy in Characterization of Samples and Concept of Infrared Spectroscopy-Based Synchrotron Radiation - Ayodele Temidayo Odularu (Journal of Spectroscopy)
The study explores the nitty-gritty of infrared spectroscopy. Firstly, the review gives a concise history of infrared discovery and its location in the electromagnetic spectrum. Secondly, the infrared spectroscopy is reported for its mechanism, principles, sample preparation, and application for absence and presence of functional groups determination in both ligands and coordination compounds. Thirdly, it helps in purity determination of unknown samples. Additional studies regarding this study entail infrared spectroscopy-based synchrotron radiation. It serves as a giant microscope to give detailed information of samples under investigation compared to the conventional infrared instrument. Infrared will continue to be useful to both chemical and pharmaceutical industries, in order to make chemical products and manufactured drugs put on wholesome integrity.